How can we minimise the use of regular oral corticosteroids in asthma?. (5th February 2020) - Bourdin, Arnaud; Adcock, Ian; Berger, Patrick; Bonniaud, Philippe; Chanson, Philippe; Chenivesse, Cécile; de Blic, Jacques; Deschildre, Antoine; Devillier, Philippe; Devouassoux, Gilles; Didier, Alain; Garcia, Gilles; et al.
Options to achieve oral corticosteroid (OCS)-sparing have been triggering increasing interest since the 1970s because of the side-effects of OCSs, and this has now become achievable with biologics. The Société de Pneumologie de Langue Française workshop on OCSs aimed to conduct a comprehensive review of the basics for OCS use in asthma and issue key research questions. Pharmacology and definition of regular use were reviewed by the first working group (WG1). WG2 examined whether regular OCS use is associated with T2 endotype. WG3 reported on the specificities of the paediatric area. Key "research statement proposals" were suggested by WG4. It was found that the benefits of regular OCS use in asthma outside episodes of exacerbations are poorly supported by the existing evidence. However, complete OCS elimination couldn't be achieved in any available studies for all patients and the panel felt that it was too early to conclude that regular OCS use could be declared criminal. Repeated or prolonged need for OCS beyond 1 g·year −1 should indicate the need for referral to secondary/tertiary care. A strategic sequential plan aiming at reducing overall exposure to OCS in severe asthma was then held as a conclusion of the workshop. A yearly cumulative OCS dose above 1 g should be considered unacceptable in severe asthma and should make the case for referral http://bit.ly/34GAYLX